Grim[m] Desires Recent review - V, Lorna (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Grim[m] Desires, Maresa von Stockert's, Hussein Chalayan, moda.
Dentro del apartado "Dance Now. Recent reviews".